2017
DOI: 10.1038/srep40690
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide identification, evolution and expression analysis of RING finger protein genes in Brassica rapa

Abstract: More and more RING finger genes were found to be implicated in various important biological processes. In the present study, a total of 731 RING domains in 715 predicted proteins were identified in Brassica rapa genome (AA, 2n = 20), which were further divided into eight types: RING-H2 (371), RING-HCa (215), RING-HCb (47), RING-v (44), RING-C2 (38), RING-D (10), RING-S/T (5) and RING-G (1). The 715 RING finger proteins were further classified into 51 groups according to the presence of additional domains. 700 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(40 citation statements)
references
References 60 publications
4
36
0
Order By: Relevance
“…It is tempting to speculate that the RING-G and RING-D types evolved from RING-H2 proteins and that changes were fixed during evolution. This idea is in agreement with the exclusive detection of the RING-D type in plant species belonging to the Brasicaceae family [10, 12]. Our phylogenetic analysis supports this speculation since both types are grouped with RING-H2 sequences (Fig 2).…”
Section: Discussionsupporting
confidence: 90%
“…It is tempting to speculate that the RING-G and RING-D types evolved from RING-H2 proteins and that changes were fixed during evolution. This idea is in agreement with the exclusive detection of the RING-D type in plant species belonging to the Brasicaceae family [10, 12]. Our phylogenetic analysis supports this speculation since both types are grouped with RING-H2 sequences (Fig 2).…”
Section: Discussionsupporting
confidence: 90%
“…Eighty percent of rice RING-finger proteins have been shown to possess E3 ligase activity [16,17]. At the same time, 731 RING-finger domains in 715 predicted proteins were divided into eight types: RING-H2 (371), RING-HCa (215), RING-HCb (47),RING-v (44), RING-C2 (38), RING-D (10), RING-S/T (5), and RING-G (1) [18]. A total of 756 RING domains in 734 predicted proteins were identified in the whole Brassica oleracea proteome.…”
Section: Introductionmentioning
confidence: 99%
“…Except for a large number of components related to optical responses, plant hormone regulation, growth and development, and stress were also common upstream of different VyRCHCs. This situation is in fact rather common in RING genes of all species [25][26][27][28]. Ubiquitin ligase SDIR1 regulates stress-responsive abscisic acid signal by interacting with ABRE abscisic acid response element [39].…”
Section: Discussionmentioning
confidence: 99%
“…The RING C3H2C3 gene family has since been identi ed in many plant species [25][26][27][28]. Related studies have shown that RING genes are involved in a variety of biological processes, growth and development and hormonal responses, as well as plant responses to abiotic stresses [29].…”
Section: Discussionmentioning
confidence: 99%